Blast resistant somaclonal variants of rice cultivar Bluebelle - Araújo, Leila Garcês de; Prabhu, Anne Sitarama; Filippi, Marta Cristina; Oliveira, Wilson Ferreira de (Pesquisa Agropecuaria Brasileira, 2001)
Rice blast, caused by Pyricularia grisea, is the major yield constraint in irrigated rice mainly in the State of Tocantins. The detection of genetic variability for blast resistance in susceptible cultivars such as Bluebelle, considered as a standard for superior grain quality, was the main objective of the present investigation. The adopted procedure included the induction of callus from the immature panicles, regeneration, evaluation and selection of R2 plants for blast resistance. The same procedure was repeated using three selected R2 plants. The disease assessment and selection of blast resistant plants were done in R2 and R4 generations in blast nursery. In greenhouse tests with three isolates obtained from the cultivar Metica-1 belonging to pathotypes IB-41 and IB-45 of P. grisea, all of the 47 somaclones R6 were resistant. They showed differential reaction to five isolates of somaclones and were resistant to one isolate derived from cultivar Bluebelle, while cultivar Bluebelle was susceptible to all isolates. These results indicated genetic variation for blast resistance in second step of induction and regeneration of plants. Of these 47 somaclones R6, 22 showed a high degree of vertical resistance in blast nursery tests conducted at four locations and can be utilized as new blast resistant sources.